Gambaran Pelaksanaan Program Pondok Tahfidzul Qur’an Baburrahmah di Kanagarian Padang Ganting Kabupaten Tanah Datar - Brilian Bakti Rabbani; Wisroni Wisroni; Irmawita Irmawita (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2018)
This research was motivated by the success of the Baburrahmah Tahfidzul Qur'an, because there was a significant increase in the number of santri within the six months since the establishment of the Baburrahmah Qur'an Tahfidzul Qur'an. The purpose of this study was to describe the implementation of the tahfidz program in terms of coordination between the implementers, program administration, and the application of the tahfidz program rules. This type of research is quantitative descriptive. The population in this study were students in Pondok Tahfidzul Baburrahmah Qur'an, totaling one hundred and fifty people and the sample in this study amounted to thirty-five people. The sampling technique in this study is stratified random sampling. Data collection techniques using structured interview techniques and data analysis techniques were obtained using a percentage formula. The results of the study show that: the Baburrahmah Pondok Tahfidzul Qur'an program is categorized very well.Keywords: Program Implementation, Tahfidzul Qur'an